Comparative effectiveness of physical exercise interventions for chronic non-specific neck pain: a systematic review with network meta-analysis of 40 randomised controlled trials. Issue 13 (2nd November 2020) - de Zoete, Rutger MJ; Armfield, Nigel R; McAuley, James H; Chen, Kenneth; Sterling, Michele
Abstract : Objective: To compare the effectiveness of different physical exercise interventions for chronic non-specific neck pain. Design: Systematic review and network meta-analysis. Data sources: Electronic databases: AMED, CINAHL, Cochrane Central Register of Controlled Trials, Embase, MEDLINE, Physiotherapy Evidence Database, PsycINFO, Scopus and SPORTDiscus. Eligibility criteria: Randomised controlled trials (RCTs) describing the effects of any physical exercise intervention in adults with chronic non-specific neck pain. Results: The search returned 6549 records, 40 studies were included. Two networks of pairwise comparisons were constructed, one for pain intensity (n=38 RCTs, n=3151 participants) and one for disability (n=29 RCTs, n=2336 participants), and direct and indirect evidence was obtained. Compared with no treatment, three exercise interventions were found to be effective for pain and disability: motor control (Hedges' g, pain −1.32, 95% CI: −1.99 to −0.65; disability −0.87, 95% CI: –1.45 o −0.29), yoga/Pilates/Tai Chi/Qigong (pain −1.25, 95% CI: –1.85 to −0.65; disability –1.16, 95% CI: –1.75 to −0.57) and strengthening (pain –1.21, 95% CI: –1.63 to −0.78; disability –0.75, 95% CI: –1.28 to −0.22). Other interventions, including range of motion (pain −0.98 CI: −2.51 to 0.56), balance (pain −0.38, 95% CI: −2.10 to 1.33) and multimodal (three or more exercises types combined) (pain −0.08, 95% CI: −1.70 to 1.53) exercises showed uncertain or negligible effects. The quality of evidence was very low according to the GRADE (Grading of Recommendations Assessment, Development and Evaluation) criteria. Conclusion: There is not one superior type of physical exercise for people with chronic non-specific neck pain. Rather, there is very low quality evidence that motor control, yoga/Pilates/Tai Chi/Qigong and strengthening exercises are equally effective. These findings may assist clinicians to select exercises for people with chronic non-specific neck pain. PROSPERO registration number: CRD42019126523.